PENGARUH TINGKAT IDENTIFIKASI PARTAI DAN CITRA KANDIDAT TERHADAP PERILAKU MEMILIH DALAM PILGUB JATENG 2013 (STUDI PERSEPSI MASYARAKAT DI KELURAHAN BRINGIN, SEMARANG) - Alqoumi Anshar A; Tri Cahyo Utomo; Edi Santosa (Journal of Politic and Government Studies, 2014)
THE EFFECT OF PARTY IDENTIFICATION AND CANDIDATE IMAGE TO THE VOTING BEHAVIOR IN CENTRAL JAVA GOVERNOR ELECTION 2013 This research is directed by a repeat of the election of candidates who promoted by PDI - P in the central java local election 2013, which presumably is the mass base of the party. Beside That, there is a gap between the results of the survey prapilgub and the final resultsof the election, where candidates in the survey had the highest electability as a figure of the incumbent , at the end was defeated by the candidate promoted by PDI - P is the lower level of popularity and electability. Therefore , this study aims to find answers how the influence of party identification and candidate image on voting behavior in Central Java Governor Election , 2013. As a theoretical basis, this research uses voting behavior theory, especially the psychological approach. The method that is being used in this research is the quantitative method. The sampling method that used in this research is purposive proportional sampling of 5566 respondents comprising of men and women , 98 people selected as the sample so that the study has a confident interval is 90 % and 10% margin of error. The results showed that there is a significant relationship between the image of the candidate on voting behavior . It is proved by testing the hypothesis using the Wald test in partial candidate image variable that shows the significance of 0,084 < 0,100 . Secondly , there is no significant influence of party identification on voting behavior . This is evidenced by the hypothesis test in partial identification of the party which shows the significance of 0.197 and 0.565 < 0.100 . Third , there is no significant relationship between the level of party identification and candidate images simultaneously on voting behavior . It is proved by testing the hypothesis using multinomial logistic regression analysis that indicates the significance 0.129 < 0.100 . Keywords: party ID, candidate image, voting behavior